Use of low‐cost three‐dimensional printer to simulate grasping of bronchial foreign body - Nakayama, Masayuki (Respirol Case Rep, 2018)
An 89‐year‐old man was hospitalized with severe pneumonia. Chest computed tomography showed a foreign body in the left main bronchus. We moulded a three‐dimensional (3D) model of the foreign body with a low‐cost 3D printer and found it had the shape of a tooth. We simulated grasping the model with several forceps and succeeded in grasping it with a retrieval net and shark‐tooth forceps. Bronchoscopy was performed after his respiratory condition improved. We found a dental foreign body that had accidentally moved and become stuck in the right upper bronchus. We scraped it out with a retrieval net and grasped the recess site of the foreign body with a shark‐tooth forceps as performed in the simulation. Removal was successful, and the total bronchoscopy time was 9 min. The bronchial foreign body was safely grasped and removed in a short time after simulation with several forceps using a low‐cost 3D printer.